On the issue of the conceptual sphere in cognitive linguistics - Vekilova Naila Janbakhish qizi (Studia Humanitatis, 2024)
Many modern works in the field of linguistics feature three main terms: cognitive linguistics, concept and conceptual sphere. Modern researchers, as a rule, consider the concept and the conceptual sphere as part of the concepts of cognitive linguistics quite broadly. Both notions are fairly interpreted as important mental units bordering on linguistics in all their fundamental features, attributes and parameters. At the same time, these concepts are closely related to lingvoculturology. The article attempts to reflect national realities in the conceptual sphere within the framework of cognitive linguistics. Thereby the research as a whole acquires not only a purely linguistic, but also a linguistic and cultural orientation.